Bone metastases from endocrine cancer: advances in diagnosis, treatment, and prevention - Huang, Shuzhou; Shen, Yue; Li, Hanchen; Geng, Tianxiang; Yan, Jinhong; Wang, Li; Sui, Laijian (Frontiers in Endocrinology, 2025)
Endocrine cancers, originating from hormone-producing organs, prefer to metastasize hematogenously to bone as a common site. Once considered rare, diagnosis rate of bone metastases presents a rising trend attribute to advanced imaging techniques and greater patient longevity. However, accurate diagnosis of bone metastases remains challenging. Diagnostic hurdles stem from heterogeneous metastatic mechanisms among cancer types and high rates of therapeutic resistance. Preventive measures remain sub-optimal, and clinical management pathways are often fragmented. Addressing these complexities requires a systematic research approach to enhance diagnostic accuracy and optimize therapeutic strategies. Present review synthesizes recent progress in the diagnosis, management, and prevention of bone metastases in endocrine tumors, emphasizing the imperative for an integrated diagnostic paradigm that leverages clinical assessment, advanced imaging, and molecular/genomic profiling to inform precision medicine. We also explore emerging hybrid predictive models that clarify the distinct biological mechanisms underpinning bone metastasis in various endocrine cancers. Ultimately, this review identifies pathways for improved therapies, refined clinical guidelines, and enhanced multidisciplinary collaboration, aiming to extend survival, improve quality of life, and ensure optimal healthcare resource utilization for patients with endocrine malignancies.